Optimization of a Niacinamide Moisturizing Cream Formula Using a Combination of Virgin Coconut Oil and Tea Tree Oil as the Oil Phase - Rahmat Muliadi; Vica Aspadiah; Suryani; Wa Ode Sitti Zubaydah; Fery Indradewi Armadany; Purnama Alia Rizki (Journal of Pharmaceutical and Natural Resources, 2025)
The skin is one of the most important organs of the body to function as a protective barrier against the prevention of water and electrolyte loss. This causes dry skin to look dull, scaly, rough surface, and evenly dry white areas. then facial skin care is needed, one of which is to use moisturizers containing ingredients that work with mechanisms (occlusive), (humectant), and (emollient). The dosage form of moisturizer that is often used is cream. The combination of VCO and tea tree oil as active ingredients in this moisturizing cream formula is expected to have a synergistic effect in increasing the effectiveness of the cream in overcoming dry skin. VCO and tea tree oil are safe to use in skin moisturizing formulations. the purpose of this study is to determine the Optimization of the Niacinamide Moisturizing Cream Formula Combination of VCO and Tea tree oil as an Oil Phase and use a Software Design Expert to determine the physical characteristics and stability of the preparation. Optimization of moisturizing cream formula using factorial design method 22 with VCO factor and Tea tree oil and using viscosity response, dispersion, and adhesion. The stability test compares tests from organoleptic, pH, dispersion, adhesion, and homogeneity before and after phase separation tests and cycling tests. Based on the test results of this study, an optimum formula using VCO and Tea tree oil was obtained showing good dosage characteristics in the form of good organoleptic tests, viscosity before cycling test 12328.735 and after cycling test 12328.731, average pH 6.1 before cycling test and 6.5 after cycling test, average dispersion 6.6 before cycling test and cycling test 6.6, Adhesion 86.33 seconds before cycling test and after cycling test 85.67 seconds after cycling test and homogeneity test showed homogeneous preparations both before and after cycling test. All test values of the characteristics of moisturizing creams that have been stored meet the stability test requirements based on their test parameters.